Brand psychology consumer perceptions, corporate reputations - Gabay, Jonathan (Kogan Page, 2015)
"Revealing the hidden processes behind why certain brands command our loyalty and trust, Brand Psychology looks at how to build up a positive brand image through Corporate Social Responsibility and ethical transparency. Reputation management authority Jonathan Gabay takes readers on a tour of the corporate, political and personal brands whose understanding of consumer psychology has either built or broken them, with examples such as e-cigarette legislation, the London 2012 Olympics, the iPhone 5S's fingerprint ID technology and Miley Cyrus.He answers key questions about brand and reputation management, including: --Why do we trust some brands more than others? --How important is integrity for a brand's survival? --How can brand confidence be rebuilt during a crisis? Combining practical, how-to advice on media relationships and crisis management, with an exploration of reputation psychology and consumer motivation. Brand Psychology reveals how to build a meaningful brand that resonates with the public"-- Provided by publisher.